Non-centrifugal sugar (NCS) and health: a review on functional components and health benefits - Zidan, Dina; Azlan, Azrina (MDPI, 2022)
Non-centrifugal sugar (NCS) is the scientific term the Food and Agriculture Organization (FAO) uses to define a solid product, produced by sugarcane juice evaporation, which is unrefined or minimally refined. NCS is referred to in various names globally, the most significant ones are whole cane sugar, panela (Latin America), jaggery (India) and kokuto (Japan). NCS contains minerals, bioactive compounds, flavonoids and phenolic acids, which have therapeutic potentials from time immemorial. Even though the bioactive property is dependent on the composition, which relies mainly on the agronomic conditions and production process, NCS possesses antioxidant and anti-inflammatory properties. Hence, substituting the consumption of refined sugar with NCS might be helpful in the control of chronic diseases generally connected to oxidative stress and inflammation. Experimental facts from in vitro and in vivo models have proven that NCS plays an essential role in weight management, maintaining insulin sensitivity and preventing neurodegenerative diseases. NCS has also shown hypoglycemic and hypolipidemic effects. This review aims to synopsize the recent literature pertaining to the benefits of NCS in human health. The NCS can be considered a nutraceutical and functional food. However, detailed and regulated studies are important to enhance the beneficial effects in human and animal interventions.